2022
DOI: 10.3390/biom12020274
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP7 Concentration May Reflect Subclinical Myocardial Damage and Kidney Function in Patients with Stable Ischemic Heart Disease

Abstract: The objective of this study was to determine the associations between insulin-like growth-factor-binding protein 7(IGFBP7) concentrations and concentrations of troponin T(TnT), N-terminal pro-B-type natriuretic peptide(NT-proBNP) and the parameters of kidney function in patients with stable ischemic heart disease(IHD). The IHD group consisted of 88 patients, and the population group comprised 66 subjects without a history of IHD. IGFBP7, TnT and NTproBNP concentrations were measured. The IGFBP7 value was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…In patients affected by ischemic heart disease (IHD), Lisowska et al found an average 1.25-fold increase in IGFBP7 serum levels in comparison to the population (1.76 ± 1 ng/mL vs. 1.43 ± 0.44 ng/mL, respectively, p = 0.019) [ 69 ]. Regarding our study, most of the patients grouped under the category of cardiovascular diseases exhibited solely arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients affected by ischemic heart disease (IHD), Lisowska et al found an average 1.25-fold increase in IGFBP7 serum levels in comparison to the population (1.76 ± 1 ng/mL vs. 1.43 ± 0.44 ng/mL, respectively, p = 0.019) [ 69 ]. Regarding our study, most of the patients grouped under the category of cardiovascular diseases exhibited solely arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that tumor markers can be altered by certain comorbidities. There are studies that show an association between specific comorbidities and IGFBP7 or ANXA1 [ 69 , 70 , 83 ]. As blood samples for our study were taken from all patients the day before surgery or panendoscopy as part of the standard preoperative examination, acute inflammatory processes or exacerbations of disease can be reliably excluded, as the patients would otherwise not have been applicable for the operation.…”
Section: Discussionmentioning
confidence: 99%
“…GPCR ligand binding [60], extracellular matrix organization [61], cytokine signaling in immune system [62], interferon signaling [63], signaling by GPCR [64], neuronal system [65] and platelet activation, signaling and aggregation [66] plays an important role in the schizophrenia. Studies have revealed that SIX1 [67], VIP (vasoactive intestinal peptide) [68], GATA6 [69], FRZB (frizzled related protein) [70], CD40 [71], WT1 [72], PCDHGA3 [73], TFAP2B [74], HFE (homeostatic iron regulator) [75], NKX2-5 [76], IGFBP7 [77], HLA-F [78], CCL2 [79], COL1A2 [80], RUNX1 [81], TFF3 [82], IRX4 [83], NOS1 [84], DKK2 [85], IL18R1 [86], ADAM12 [87], NPPC (natriuretic peptide C) [88], COL1A1 [89], ABCG2 [90], SIX2 [91], CSRP1 [92], MR1 [93], NINJ2 [94], ACE (angiotensin I converting enzyme) [95], TBX1 [96], CTSC (cathepsin C) [97], DLX6 [98], KCNE1 [99], AZGP1 [100], CYP1B1 [101], PRRX1 [102], CD34 [103], A2M [104], CDKN2A [105], SERPINE1 [106], CD44 [107], FABP4 [108], ITGB3 [109], ALOX5AP [110], DAND5 [111], SFRP4 [112], RUNX2 [113], TACR3 [114], MYD88 [115], CYBA (cytochrome b-245 alpha chain) [116], STAT6 [117], FOXC1 [118], FN1 [119], TLR6 [120], CAV1 [121], RGS4 [122], TPM2 [123], TNFSF4 [124], LOX (lysyl oxidase) [125], SMOC2 [126], SPHK1 [127], FOLH1 [128], CYP2C8 [129], CD163 [130], DIRAS3 [131], OSMR (oncostatin M receptor) [132], POSTN (peri...…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that IGFBP7 was found as a new biomarker for a variety of disorders, including heart failure, cardiomegaly, etc. The IGFBP7's function in the development and evolution of diabetes, acute kidney injury (AKI), obesity, chronic obstructive pulmonary disease (COPD), malignancies, and other diseases has been investigated in a number of research14 .2023, 20(3 Suppl. ): 979-985 https://dx.doi.org/10.21123/bsj.2023.7797 P-ISSN: 2078-8665 -E-ISSN: 2411-7986 Baghdad Science Journal…”
mentioning
confidence: 99%